Boulders in the Stream: The Lineage and Founding of the Society for the Anthropology of Consciousness - Schwartz, Stephan A. (Anthropology of consciousness, 2021)
The founding of the Society for the Anthropology of Consciousness (SAC) can only be understood within the cultural context of its heritage. This paper is an historical narrative tracing the intellectual lineage of the SAC. The immediate causes were a series of symposia in 1974, including several on the challenge to anthropology represented by Carlos Castaneda, who attacked the way a critical part of anthropology was conducted. The argument in his own narrative was that one could not understand the shamanic world view without becoming a shaman. No informant could ever convey this, because so much of it was experiential. It could not be properly known unless one entered with sincerity into the experience, as a participant not just an observer. Two insights central to this thesis are particularly relevant to SAC: an aspect of human consciousness exists independent of time and space susceptible to volitional control; and, there is an interconnection between all life forms, which must be understood if the universal impulse humans feel toward the spiritual component of their lives is to properly mature. The SAC can be seen in pure Kuhnian terms as one response to the reassessment that Castaneda forced on anthropology.